Association Between Maternal Height and Childhood Stunting in Indonesia: A Systematic Review - Yanasta Yudo Pratama; Muhammad Luthfi Adnan (Universitas Ahmad Dahlan, 2026)
Background: Stunting is one of Indonesia's most complex health problems with the incidence of stunting reaches almost 30%. Maternal factors are known to play a significant role in the risk of stunting. However, further analysis of the influence of maternal height is needed to identify the influence of maternal height on child growth and development for future intervention. This study aims to evaluate maternal height as risk factor for stunting in Indonesia based on previous published article. Method: This systematic review was prepared in accordance with the PRISMA guidelines. The literature search was conducted in PubMed and Google using keywords in English including